Characterisation of the periodontal proteome in gingival crevicular fluid and saliva using SWATH-MS - Triana Blanco-Pintos; Alba Regueira-Iglesias; Berta Suárez-Rodríguez; Noelia Seijas-Otero; Marta Relvas; Susana B. Bravo; Carlos Balsa-Castro; Inmaculada Tomás (Frontiers in Cellular and Infection Microbiology)
IntroductionProteomic techniques are useful to analyse the periodontal proteome in gingival crevicular fluid (GCF) and saliva. However, few investigations have assessed and compared the GCF and salivary proteomes. Therefore, this research aims to analyse the proteome structure and compare protein expression in these fluids between individuals with periodontal health and those with periodontitis.MethodsGCF and saliva were collected from 44 periodontally healthy subjects and 41 with periodontitis (stages III-IV). Samples were analysed using sequential window acquisition of all theoretical mass spectra (SWATH-MS), and proteins were identified employing the UniProt database. The periodontal proteome structure was assessed using principal component analysis (PCA). Differential protein expression was defined as an adjusted p-value <0.05 combined with a fold-change ≥2 (upregulated) or ≤0.5 (downregulated).Results250 abundant proteins were quantified in GCF and 377 in saliva (238 in common). The proteome structure was different in periodontitis compared to periodontal health in both oral fluids. In GCF, 63 (25.2%) proteins were differentially expressed, with 38 upregulated and 25 downregulated in periodontitis. The most overexpressed proteins were haemoglobin subunits (Hbs) beta (fold-change of 5.06) and alpha (4.35), carbonic anhydrase 1 (4.28), and protein S100-P (4.27). Among the underexpressed proteins, 14 were keratins, with type II cytoskeletal 6B being the most downregulated (0.10), together with glyceraldehyde-3-phosphate dehydrogenase (0.12) and zymogen granule protein 16 homolog B (0.13).In saliva, 59 (15.7%) proteins were differentially expressed, with 55 upregulated and four downregulated in periodontitis. Twenty-nine proteins showed a fold-change ≥4, highlighting beta-2-microglobulin (44.14), keratin, type I cytoskeletal 13 (36.23), neutrophil defensin 1 (25.08), proteins S100-A9 (12.30), A8 (10.61), A12 (4.76), and P (4.72), annexin A1 (9.34), lysozyme C (4.98), immunoglobulin heavy constant alpha 1 (4.45), resistin (4.37), and Hbs beta (4.20) and alpha (4.06). The most downregulated protein was lipocalin-1 (0.35). Fourteen proteins were differentially expressed in GCF and saliva, where seven were keratins being underexpressed in GCF but overexpressed in saliva.ConclusionPeriodontitis alters the periodontal proteome structure and the expression of numerous abundant proteins in GCF and saliva. However, proteins expressed vary qualitatively and quantitatively, indicating different expression patterns between oral fluids.